2013
DOI: 10.1111/jdi.12177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical profile of diabetes mellitus in productive aged urban Indonesians

Abstract: Aims/IntroductionTo estimate the prevalence and clinical profile of diabetes mellitus in productive aged urban Indonesians based on the National Basic Health Research 2007.Materials and MethodsThe statistical analyses of a cross‐sectional survey included the data of 15,332 adults, aged 18–55 years, living in an urban area. Blood glucose was measured by an automatic clinical chemistry analyzer by 2‐h, 75‐g post glucose load after an overnight fast. Weight, height, waist circumference and blood pressure data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 15 publications
7
50
0
7
Order By: Relevance
“…20 Mihardja et al, in contrast, suggested that diabetes mellitus affected more women than men which increased with age and body mass index. 21 The occurence of the diabetes was highly correlated with hypertension. Whereas, Widjaja et al, reported that within sex groups, the prevalence of prehypertension was higher in females.…”
Section: Discussionmentioning
confidence: 99%
“…20 Mihardja et al, in contrast, suggested that diabetes mellitus affected more women than men which increased with age and body mass index. 21 The occurence of the diabetes was highly correlated with hypertension. Whereas, Widjaja et al, reported that within sex groups, the prevalence of prehypertension was higher in females.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus as one of the non-communicable diseases (PTM) has a high prevalence in Indonesia. The prevalence of diabetes mellitus in Indonesia based on doctor's diagnosis and symptoms experienced by patients reaches 6.9% or around 12 million people through respodent Indonesian society over 15 years [2]. Uncontrolled diabetes mellitus causes 2.2 million deaths due to cardiovascular risk factors and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, research results on diabetes prevalence rates usually do not distinguish between diabetes type 1 and 2 (Mihardja et al. ; National Institute for Health Research and Development ; Soegondo et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…) and wide‐ranging approaches are required for screening, preventing and managing diabetes and the complications (Mihardja et al. ). These management approaches need to involve healthcare professionals (HCPs) from various health disciplines (Soewondo et al.…”
Section: Introductionmentioning
confidence: 99%